2011
DOI: 10.7589/0090-3558-47.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and Hematologic Responses to Surgically Implanted Transmitters in Eastern Massasauga Rattlesnakes (Sistrurus Catenatus Catenatus)

Abstract: ABSTRACT:The study of secretive snakes, such as rattlesnakes, has benefited from the use of radiotelemetry. However, the principal assumption in telemetry studies is that the transmitter has no significant effect on the study animal. To test the validity of this assumption, the physiologic and pathologic effects of intracoelomic implants were examined in a group of 24 eastern massasauga rattlesnakes (Sistrurus catenatus catenatus) in a laboratory setting over a period of 58 wk between March 2005 and April 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 41 publications
(39 reference statements)
0
15
1
1
Order By: Relevance
“…Hemoglobin was significantly lower compared with snakes without implants (Lentini et al, 2011). Increases in these leukocyte counts were not as pronounced in our study at the three transmitter sampling stages; however, reduced Hb concentration at the last two sampling stages may indicate an anemic response, similar to that found by Lentini et al (2011).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Hemoglobin was significantly lower compared with snakes without implants (Lentini et al, 2011). Increases in these leukocyte counts were not as pronounced in our study at the three transmitter sampling stages; however, reduced Hb concentration at the last two sampling stages may indicate an anemic response, similar to that found by Lentini et al (2011).…”
Section: Discussioncontrasting
confidence: 50%
“…These parameters may reflect hydration or nutritional status. A study by Lentini et al (2011), specifically designed to test the inflammatory response of implanting radiotransmitters in rattlesnakes (Sistrurus catenatus catenatus), found that 33% of implanted snakes had grade 3 or higher reactions (on the basis of histopathologic tissue examination) with extensive and active inflammation. The reaction to the implant FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…We surgically implanted massasaugas with 1 of 3 radiotransmitters of varying mass, depending on body mass (models R1515, 7 g, and R1680, 3.1 g, Advanced Telemetry Systems, Inc., Isanti, MN, USA; model SB‐2, 5.3 g, Holohil Systems Ltd., ON, Canada) following Bailey () and Bailey et al (). The combined mass of the implanted radiotransmitter and PIT tag did not exceed 5% of body mass (Lentini et al ). Implanted massasaugas were approved for release by the veterinarian and subsequently released at their original capture location after up to 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…(Mattison, 1995). 따 라서 기본적으로 발신기 삽입 수술방법을 이용한 연 구에서는 발신기 삽입이 연구 동물의 생존에 영향을 미치지 않는다는 가정 하에 연구를 진행해야 한다 (Gursky, 1998;Millspaugh and Marzluff, 2001 Karesh, 1989;Olsen et al, 1992;Rudolph et al, 1998;Murray and Fuller, 2000;Godfrey et al, 2003;Lentini et al, 2011 (Kenward, 1987;White and Garrott, 1987)로 권고하고 있으며, 곤충의 경우 10% 이내 (Cant et al, 2005), 어류의 경우 2% 이내 (Winter, 1983), 양 서류의 경우 10% 이내 (Richards et al, 1994;Jehle and Arntzen, 2000)로 분류군마다 다양하게 권고하고 있다. 파충류인 뱀의 경우, 발신기 삽입 수술을 이용한 여 러 선행연구들에서 대상개체의 전체 체중에 대한 발 신기무게비율을 적게는 1% 에서 많게는 7% 이내 까 지 권고하고 있다(e.g.…”
Section: 서 론unclassified